The Impact of a Training Program Based on Learning Needs on Self-Care Behaviors among Patients with Heart Failure - Seyedeh Fatemeh Gheiasi; Mahin Roohani; Nasrin Hanifi; Kourosh Kamali (Mashhad University of Medical Sciences, 2017)
Abstract Background: Heart failure necessitates self-care; therefore, self-care training should be based on learning needs (LNs) of patients. Aim: This study aimed to determine the impact of a training program based on learning needs on self-care behaviors among patients with heart failure Method: This clinical trial was performed on 73 patients suffering from heart failure in Zanjan teaching hospitals in 2015. The subjects were randomly divided into three groups (based on having LNs assessment and family involvement). The intervention group received education based on LNs and family involvement.   Control group 1 (without LNs assessment with family involvement), and control group 2 (without LNs assessment, and family involvement). The groups received three sessions of face-to-face training (lasting 15-20 minutes) on medical symptoms, necessary measures for the disease, diet, and medication regimen. Self-care behaviors before and 90 days after the intervention were evaluated using a self-care of heart failure index. To analyze the data, analysis of variance (ANOVA) and Bonferroni post-hoc test were used in SPSS, version 11. Results: The mean age of the participants was 65.5±14.1 years. According to the results of ANOVA, the total self-care score before the intervention was not significantly different among the three study groups (P